Fulleropyrrolidine-functionalized ceria nanoparticles as a tethered dual nanosystem with improved antioxidant properties. Issue 6 (7th May 2020) - Pinna, Alessandra; Cali, Eleonora; Kerherve, Gwilherm; Galleri, Grazia; Maggini, Michele; Innocenzi, Plinio; Malfatti, Luca
Abstract : Combining nanoceria and fulleropyrrolidine in a tethered nanosystem allows for efficient scavenging of reactive oxygen species and improved protection of mouse fibroblast cells exposed to a UV insult. Abstract : Dual-tethered nanosystems which combine different properties at the nano scale represent a new fascinating frontier of research. In the present work, we present an example of a dual nanosystem designed to enhance the radical scavenging performances. Fulleropyrrolidine has been bonded to cerium oxide nanoparticles (nanoceria) to form a dual tethered system. Fulleropyrrolidine, bearing a silyl-alkoxide group, has been chemically bonded to the nanoceria surface, providing unprecedented antioxidant activity. This effect has been evaluated using an L929 mouse fibroblast cell line exposed to UV light. The fulleropyrrolidine molecules tethered to nanoceria enhance the radical scavenging properties of the oxide. At the same time, fulleropyrrolidine mitigates the potential toxicity of nanoceria at high doses. On the other hand, cerium oxide nanoparticles provide a strong hydrophilicity to the dual nanosystem, ensuring the administration in a cellular environment and preventing macroscopic aggregation of fulleropyrrolidine. The rational assembly of two different components in one nanosystem appears as a promising route for the development of "smarter" medical and cosmetic devices.